Toleransi sebagai Model Relasi Kerukunan Umat Beragama dalam Pendidikan Kristiani - Panggabean, Justice Zeni Zari (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2022)
Tolerance in the context of religion is an attitude of mutual respect, mutual respect in practicing the equality of religious teachings, and cooperation in social and state life. Tolerance as a model of religious harmony can be done by teaching and practicing their respective religions. The problems that occur are often the teaching of religious education, tolerance is carried out excessively so that it instills unhealthy doctrine for its adherents. The paper aims: first, to explain tolerance as a model of religious harmony; the second describes the concept of teaching Christian education as a reflection of sensitivity to knit religious harmony; the third offer a solution to the problem of low tolerance due to ethnic stereotypes of fanaticism. The importance of an attitude that is able to maintain harmony in inter-religious communication that leads to religious harmony. The method used is a qualitative research approach that describes the study of tolerance as a model of religious harmony in Christian education. The data was used to describe some of the literature related to the topics discussed. The result indicates that teaching Christian education is a forum for fostering a model of togetherness and religious harmony associated with the subject matter. The conclusion of the embodiment of tolerance as a model of the relationship of religious harmony invites the empathetic thinking power of educators and students to create an atmosphere of peace and religious security. In this case, tolerance as a model of religious harmony in Christian education minimizes conflict in the name of religion as a way to prevent discrimination against a religion. AbstrakToleransi dalam konteks agama berkaitan dengan sikap yang didalamnya ada rasa menghormati, menghargai pengamalan ajaran agama dalam kesetaraan dan kerja sama, baik kehi-dupan bermasyarakat maupun bernegara. Toleransi sebagai model relasi kerukunan umat beragama dapat dilakukan dengan upaya pengajaran dan pengamalan masing-masing agama. Permasalahan dalam pendidikan agama, adalah menanamkan doktrin yang kurang sehat bagi para pemeluknya secara berlebihan. Tujuan dalam tulisan ini yaitu: pertama, menguraikan toleransi sebagai model relasi kerukunan umat beragama; kedua mendeskripsikan konsep pengajaran pendidikan kristiani sebagai refleksi kepekaan untuk merajut kebersamaan kerukunan umat beragama; ketiga menawarkan dialog sebagai dasar toleransi kerukunan umat beragama. Pentingnya sikap yang mampu menjaga keharmonisan dalam komunikasi antar umat beragama yang mengarah pada kerukunan umat beragama. Metode yang digunakan adalah pendekatan penelitian kualitatif yang mendeskripsikan kajian toleransi sebagai model kerukunan umat beragama dalam pendidikan Kristiani. Data yang digunakan menguraikan beberapa literatur yang berkaitan dengan topik yang diahas. Hasil penelitian menunjukkan bahwa pengajaran pendidikan kristiani merupakan wadah memupuk model kebersamaan dan kerukunan umat beragama yang dikaitkan dalam materi pelajaran. Kesimpulan dalam penelitian ini adalah perwujudan toleransi sebagai model relasi kerukunan umat beragama mengundang daya berpikir empati para pendidik dan nara didik untuk menciptakan suasana damai dan aman bagi agama-agama. Dalam hal ini, toleransi sebagai model kerukukan umat beragama dalam pendidikan Kristiani meminimalisir konflik yang mengatasnamakan agama sebagai pencegahan perlakuan diskriminasi terhadap suatu agama.